SAMHD1 in Retroviral Restriction and Innate Immune Sensing – Should We Leash the Hound? - Herrmann, Alexandra; Happel, Anna-Ursula; Gramberg, Thomas (Current HIV Research, 2016)
Background: The antiviral restriction factor SAM domain and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase and thereby contributes to the regulation of intracellular dNTP levels. SAMHD1 blocks retroviral infection at the level of reverse transcription in myeloid cells and resting CD4+ T cells and is counteracted by the accessory protein Vpx, which is encoded by human immunodeficiency virus 2 (HIV-2) and several simian immunodeficiency virus (SIV) strains. Recently, it has been shown that the antiviral activity of SAMHD1 in myeloid dendritic cells (DC) hampers the induction of an efficient immune response directed against HIV-1. Conclusion: Within this review, we will summarize recent advances on the biology of SAMHD1 and its function as an antiviral restriction factor. In addition, we will discuss its role in autoimmunity and the antiviral immune response directed against HIV-1 and will evaluate the possibility of modulating SAMHD1 activity to generate an enhanced antiretroviral immune response.
Keywords: HIV